Beyond Misconceptions: Assessing Pain in Children with Mild to Moderate Intellectual Disability - Zabalia, Marc (Frontiers in Public Health, 2013)
To assess and manage pain in children and adolescents with mild to moderate intellectual disability, healthcare providers need access to updated tools and current knowledge. Recent studies show that these children can verbally express pain and use self-assessment tools accurately. Moreover, they know pain coping strategies. Finally, they show mental imaging skills and are able to recall autobiographical memories. These new data suggest that such children and adolescents could be candidates to for hypno-analgesia protocols and behavioral relaxation